Pengelolaan Sampah Berbasis Jiwa Gotong Royong - Munawaroh, Siti; Hamid, Darwan; Harun, Galian Ramdani; Susanti, Reza Septi; Nugraha, Muhammad Adi; Handayani, Sri; Suwarni, Suwarni; Wahyudi, Yusuf (Universitas Dehasen Bengkulu, 2025)
Waste is a crucial issue faced by various regions, especially in densely populated areas. One potential approach to addressing this problem is through a mutual cooperation-based waste management model. This community service aims to study the effectiveness of waste management by involving active community participation in the spirit of togetherness and collective responsibility. The methods used include literature studies, field observations, and interviews with residents and environmental administrators. The results of community service show that the mutual cooperation approach not only increases environmental awareness, but also strengthens social relations and reduces the volume of waste disposed of at the landfill. The success of the program is highly dependent on local leadership, ongoing education, and regulatory support from the local government. Therefore, this model is worthy of being a strategic alternative in community-based waste management. The main factor that plays an important role in creating a clean, waste-free environment is community participation in managing waste. One form of community participation in waste management is mutual cooperation. Poor waste management can have a negative impact on the health, environment, socio-economics and culture of the community. Community service activities aim to increase the knowledge and understanding of village communities in managing community-based waste. The community service method used is counseling with material on the waste bank waste management model, principles and values ​​of mutual cooperation in rural areas and empowerment of rural communities. The results of the community service show that the community in Pematang Gubernur Village,Muara Bangka hulu District, Bengkulu City understands the waste bank waste management model, principles and values ​​of mutual cooperation in rural areas and empowerment of rural communities and is able to implement community-based waste management methods so that a clean and comfortable environment is created.